Prevalence of metabolic syndrome in patients with chronic obstructive pulmonary disease: An observational study in South Indians. Issue 4 (July 2020) - Priyadharshini, N.; Koushik Muthu, Raja M.; Renusha, R.C.; Reshma, S.; Sindhuri Sai, Marella; Rajanandh, M.G.
Abstract: Background and aims: Metabolic syndrome (MetS) has a significant association with airflow obstruction and physical inactivity, which are the relevant extra-pulmonary markers of chronic obstructive respiratory disease (COPD). This study aimed to estimate the prevalence of MetS and its correlation with comorbidities and health related quality of life (HRQoL) in South Indian patients with COPD. Methods: A cross-sectional study was conducted among the 76 COPD patients. Pulmonary function test (PFT) and parameters for MetS such as waist circumference, blood pressure, fasting blood glucose, triglycerides (TGs) and high density lipoprotein cholesterol (HDL-C) levels of COPD patients were measured. HRQoL was calculated using Saint George Respiratory Questionnaire (SGRQ). Results: 54% of COPD patients were presented with MetS especially in stage II and III. TGs and HDL-C were significantly associated with the severity of COPD ( p < 0.05), while waist circumference, TGs and HDL-C were significantly ( p < 0.05) correlated with PFT. Symptom, activity, impact and total scores of SGRQ was increased statistically ( p < 0.05) in COPD patients with MetS than without MetS. Conclusion: According to our findings, screening the grade II and III COPD patients for the presence of MetS is a reasonable option. The results of this study should be confirmed with a larger sample of population. Highlights: More than one half of the chronic obstructive pulmonary disease (COPD) patients have metabolic syndrome (MetS). SGrade II and III COPD patients can be screened for MetS option before succumbing to any life threatening events of MetS. MetS being common in COPD patients, developing a therapeutic strategy for COPD patients can modify the MetS.